PENGARUH CURRENT RATIO DAN RETURN ON EQUITY (ROE) TERHADAP EARNING PER SHARE (EPS) - Deni Sunaryo; Yuda Supriatna; Yoga Adiyanto (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2019)
This study aims to determine the Influence of Current Ratio and Return on Equity (ROE) on Earning Per Share (EPS) in food and beverages manufacturing companies listed in Indonesia Stock Exchange Period 2013-2017. This research was conducted by using assosiative method and using quantitative approach. The population in this study amounted to 18 companies food and beverages. The sample uses purposive sampling technique as data collection technique. The number of samples used in the study were 13 food and beverages companies listed in Indonesia Stock Exchange for the period 2013-2017. The method used in this research is descriptive statistics and data analysis using classical assumptions, hypothesis test data using multiple linear regression analysis. Data in this research is processed by using program of SPSS version 23. Based on the results of this study can be concluded that the partial test (t test) shows that the independent variable Current Ratio significant effect on the dependent variable Earning per Share, while the independent variable Return on Equity (ROE) has no significant effect on Earning per Share. Based on the simultaneous test (Test F) shows that the independent variable Current Ratio and Return on Equity (ROE) together have no significant effect) on Earning per Share (EPS) with significance value of 0.109 greater than 0.05.